Glycan expression profile of signet ring cell gastric cancer cells and potential applicability of rBC2LCN-targeted lectin drug conjugate therapy - Yang, Yu; Akashi, Yoshimasa; Shimomura, Osamu; Tateno, Hiroaki; Saito, Sayoko; Hiemori, Keiko; Miyazaki, Yoshihiro; Furuta, Tomoaki; Kitaguchi, Daichi; Kuroda, Yukihito; Pakavarin, Louphrasitthiphol; Oda, Tatsuya (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2022)
Background Signet ring cell carcinoma (SRC) is a distinct subtype of gastric cancer (GC); however, the specific characteristics of cancer cell surface glycans and glycosylation remain unclear. In this study, we investigated SRC-specific glycans using lectin microarray and evaluated the potential applicability of a glycan-targeting therapy. Methods SRC cell lines (NUGC-4 and KATO-III) and non-SRC (NSRC) cell lines (NCI-N87, SNU-1, and MKN-45) were subjected to lectin microarray analysis to identify the SRC-specific glycans. Additionally, we performed immunohistochemical lectin staining and evaluated the anti-tumor effects of lectin drug conjugates (LDCs) using high-affinity lectins for SRC. Results Among the 96 lectins tested, 11 high-affinity and 8 low-affinity lectins were identified for SRC. Glycan-binding motifs varied in the high-affinity lectins, but 5 (62.5%) low-affinity lectins bound the same glycan structure, α2–6-linked sialic acids. The ratio of signal intensity in SRC to NSRC (SRC/NSRC) was highest in the rBC2LCN lectin (1.930-fold), followed by the BPL lectin (1.786-fold). rBC2LCN lectin showed high affinity for both SRC cell lines and one of the three NSRC cell lines (NCI-N87). The therapeutic effects of the LDC, rBC2LCN-PE38 (rBC2LCN, and Pseudomonas exotoxin A), showed cytocidal effects in vitro and tumor regression in in vivo mouse xenograft models. Conclusion We reported specific glycan profiles in SRC cells, showing reduced α2–6-linked sialic acids. Additionally, we found a targeted therapy using rBC2LCN lectin might be applicable as an alternative treatment option for patients with SRC.